2004
DOI: 10.1037/0893-3200.18.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Marital Relationships.

Abstract: As most adults will marry at least once during their lifetime, studying marital quality and its predictors is of great importance. The current study addresses (a) the extent of agreement between husbands and wives on their marital quality, (b) genetic and environmental sources of individual differences on spouse reports of marital quality, and (c) the extent to which genetic and environmental influences account for overlap of spouse reports on marital quality. Adult Swedish twin women and their partners partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
84
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 30 publications
19
84
1
Order By: Relevance
“…Some of the twins in this study who were in this kind of relationship were also competitive as regards their marriage partner, while those twins who were dependent on each other were intruding on the marriage of the co-twin. In contrast to earlier genetic studies, where the choice of partner has been considered either as attributive to the genetic origin of the twins (Jerskey et al, 2010;Spotts et al, 2004) or that twins choose a partner because they want to recreate a marital relationship that resembles the twin relationship (Byng-Hall, 1995), are not supported by this study. Instead, based on the perspective of time and old age, it shows that even if the twins married out of love, twins whose spouses were related to one another or were friends before marriage continued their lives in a way where both families were involved with each other as long as they stayed married.…”
Section: Discussioncontrasting
confidence: 54%
“…Some of the twins in this study who were in this kind of relationship were also competitive as regards their marriage partner, while those twins who were dependent on each other were intruding on the marriage of the co-twin. In contrast to earlier genetic studies, where the choice of partner has been considered either as attributive to the genetic origin of the twins (Jerskey et al, 2010;Spotts et al, 2004) or that twins choose a partner because they want to recreate a marital relationship that resembles the twin relationship (Byng-Hall, 1995), are not supported by this study. Instead, based on the perspective of time and old age, it shows that even if the twins married out of love, twins whose spouses were related to one another or were friends before marriage continued their lives in a way where both families were involved with each other as long as they stayed married.…”
Section: Discussioncontrasting
confidence: 54%
“…9,20,21 For example, studies of adult twins have shown that desirable and undesirable life events are moderately heritable 22,23 as are specific life events and life circumstances, including divorce, 24,25 the propensity to marry, 26 marital quality 27 and social support. [28][29][30] Studies in which researchers have measured child-specific aspects of the environment have also shown that putative environmental factors, such as parental discipline or warmth, are moderately heritable 12 (for reviews, see Plomin and Bergeman 20 ).…”
Section: Rge: Evidence From the Behavioral Genetic Literaturementioning
confidence: 99%
“…The research conducted by the COGA group on GABRA2 illustrates this concept. Edenberg et al 45 found that GABRA2 was not only strongly linked to alcohol dependence, but also to brain oscillations in the beta frequency range (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Beta rhythms reflect a balance between excitatory and inhibitory networks of nerve cells and this balance is thought to be regulated by the GABA A receptor.…”
Section: Genotype-environment Associations: Challenges In Identifyingmentioning
confidence: 99%
“…Since traits related to mating such as jealousy are linked to fitness, it is debatable whether genetic variation, reflected through significant heritability, for these traits is expected to be found. Previous quantitative genetic studies of human mating behavior have shown evidence of genetic influences on variation in reproductive behavior and sexual monogamy (Bailey et al, 2000;Bricker et al, 2006;Cherkas et al, 2004;Mustanski et al, 2007) as well as in more social monogamy or pair-bonding-related outcomes, including maintenance of a heterosexual relationship and remarriage following separation (Trumbetta & Gottesman, 2000), marital quality (Spotts et al, 2004), and the likelihood of divorce (Jockin et al, 1996;Mcgue & Lykken, 1992). The ideal conditions needed for selection to completely diminish genetic variation for these behaviors seem to rarely exist and advances in evolutionary genetics (Keller & Miller, 2006) have presented several possible suggestions to why this could be the case.…”
Section: Discussionmentioning
confidence: 99%